The Synergy Effect: How Funding and Open Access Amplify Research Citations in Emerging Universities - Gayang, Fullstar Lamin; Wanniang, Evangelyne; Islam, Akramul (Information Research Communications, 2026)
Background We examined the interaction between Open Access (OA), research funding and citation impact from seven universities in Northeast India by studying 8616 articles between 2015 and 2024. Methodology The findings indicate that OA articles receive substantially more citations than closed access publications, with a 68% citation advantage and statistically significant differences (p<0.001). Results Funding for research makes a publication more likely to be in OA by 1.67-3.9 times, with internationally funded agencies contributing significantly more to OA (60.9-100%) than Indian national funding agencies (16.9-71.2%). We found a significant synergy between funded OA publishing and citation impact; OA articles supported by funding received 171-274% more citations than unfunded papers that were closed access. Conclusion The advantages of international collaboration were similarly strong; internationally collaborating papers received 21.9-73.1% more citations than their domestic collaboration.
Keywords: Central universities; Citation impact; Northeast India; Open access; Research funding.